Evaluasi Rekomendasi Pemupukan Hara Spesifik Lokasi (PHSL) Padi Sawah di Jawa Timur - suyamto, suyamto; Saeri, M. (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
Site Spesific Nutrient Management/SSNM (Pemupukan Hara Spesifik Lokasi/PHSL)  recommendation for rice can be obtained from the website of Indonesian Rice Consultation Service (http:/webapps.irri.org>lkp). This program was developed by International Rice Research Institutes (IRRI) in collaboration with Indonesian Agency for Agricultural Research and Development (IAARD). The objective of this study is to evaluate the PHSL recommendation for  rice through adaptive research approach. This research was conducted in two sites (Ngawi and Jember) during the dry season (April to July) 2014. Three fertilizer recommendations ware evaluated : (i) PHSL recommendation for hybrid rice (Mapan P05 variety), (ii) PHSL recommendation for inbred rice (Ciherang variety) and (iii) fertilizers practiced by farmer for inbred rice (Ciherang variety). PHSL recommendation which  assessed from the website with the yield target of 8 t/ha for Ngawi was 200 kg/ha Phonska applied at 0-14 days after transplanting, 125 kg Urea/ha applied at 24-28 days after transplanting and 200 kg Urea/ha applied at 38-42 days after transplanting. For Jember, rate of Phonska was higher (250 kg/ha) while rate of Urea was  same with Ngawi. The three fertilizer recommendations were applied by each farmer with 10 cooperator farmers as replications. The observations included soil analysis before conducting the research, fertilizers used by cooperator farmers, yield of rice and benefit analysis. Fertilizer used by 10 farmers in Ngawi showed : (i) 7 farmers applied fertilizers two times and only 3 farmers applied three times, (ii) all farmers  used organic fertilizer from 220 to 940 kg/ha, (iii) all farmers used Phonska fertilizer and applied two times, (iv) total of fertilizers applied ranged from 700 to 1,000 kg/ha. While total fertilizers of PHSL recommendation was only 475 kg/ha. The similar observations were observed in Jember, but all farmers applied fertilizers two times. Research results showed that compared to farmer’s practice, PHSL recommendation saved 26.83 kg N/ha, 55.23 kg P2O5/ha and 36.05 kg K2O/ha in Ngawi. In Jember, PHSL recommendation did not save N but saved 34.2 kg/ha P2O5 and 16.6 kg K2O/ha. Yield of inbred rice with PHSL recommendation was not different, however, yield of hybrid rice  was higher to that of farmer’s practice. It can be concluded that PHSL recommendation  save fertilizers with no yield decrease for inbred rice, or even, increased yield of  hybrid rice  It’s means PHSL recommendation increase fertilizer-used efficiency and rice farming benefit.